Changes of tumor microenvironment in non-small cell lung cancer after TKI treatments - Chen, Shanshan; Tang, Jingyi; Liu, Fen; Li, Wei; Yan, Ting; Shangguan, Dangang; Yang, Nong; Liao, Dehua (Frontiers in Immunology, 2023)
Non-Small Cell Lung Cancer (NSCLC), accounting for 85% of all lung cancer diagnoses, is the most common type in which EGFR, KRAS, and ALK mutations are the common genetic drivers. Although targeted therapies such as tyrosine kinase inhibitors(TKI) have showed a better response for oncogene-driven NSCLC than chemotherapy, the development of resistance are inevitable following the treatments. Meanwhile immunotherapy have showed few responses for oncogene-driven NSCLC. The tumor microenvironment (TME) is increasingly recognized as crucial parameter for the efficacy of cancer treatment like target therapy or immunotherapy. In fact, evidence has now shown that TME could be affected by multi-factors, such as TKIs. Here, we discuss changes of TME in NSCLC after TKI treatments, especially for EGFR TKI to offer information for a new therapy thought for oncogene-driven NSCLC.